The Qur'an as a Source of Islamic Epistemology and Its Implementation in the Contemporary Era - Ummah, Khaira; Samad , Duski; Mamad , Firdaus ST (The Future of Education Journal, 2025)
This study examines the position of the Qur'an as the foundation of Islamic epistemology and its implementation in the contemporary era. The Qur'an is not merely a spiritual guide, but also a comprehensive methodological framework for understanding reality through the bayani (textual), burhani (rational), and irfani (spiritual) approaches. This study uses a qualitative method with a literature review approach, analyzing primary sources of the Qur'an and secondary sources from classical and contemporary Islamic thought literature. The results show that Islamic epistemology integrates revelation, reason, sensory experience, and spiritual intuition as sources of knowledge. In the contemporary context, the application of the Qur'an as the foundation of epistemology is seen in various fields, including education, astronomy, embryology, and technologies such as artificial intelligence and digital ethics. The integration of bayani, burhani, and irfani approaches produces comprehensive knowledge, based on revelation as well as rational, empirical, and spiritual. This study contributes to the development of an Islamic scientific framework that is able to address contemporary challenges without losing its identity and spiritual values.